Perspektif Tindak Pidana Kartu Kredit (Carding) terhadap Putusan Pengadilan - indah Novitasari; Muhari Agus Santoso; Wika Yudha Shanty (Bhirawa Law Journal, 2020)
Credit card is the one of modern paying tools which has benefit and easy. However, the credit card can make kinds of criminal like fabrication credit card and robbing credit card data. The problem will be explain in this research are What is the judicial review toward District Court of Malang Judgment Number 6/Pid.SUs/2019/PN.MLG credit card criminal perspective, District Court of Malang Judgment Number 6/Pid.SUs/2019/PN.MLG credit card criminal perspective is already appropriate with Information and Electronic Transaction or not. Theresearch use normative law method with literature research. This research use secondary data which is obtained from act analysis that have relation with this research and another law materials consist of book, journal, and another literature. Carding criminal is the one of cybercrime. The way to handle carding criminal can use Criminal Code and Banking Act besides Information and Electronic Transaction Act.